2015
DOI: 10.1007/s00264-015-2958-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of periprosthetic femoral fractures with modular stems

Abstract: Modular femoral stems are an acceptable treatment in type B2 and B3 periprosthetic fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The excellent implant survivorship found in this study is consistent with what has previously been published 11-17,21,27-31 (Table V). Otero et al 10 reported only 1 case of aseptic femoral loosening in a series of 47 periprosthetic femoral fractures.…”
Section: Discussionsupporting
confidence: 92%
“…The excellent implant survivorship found in this study is consistent with what has previously been published 11-17,21,27-31 (Table V). Otero et al 10 reported only 1 case of aseptic femoral loosening in a series of 47 periprosthetic femoral fractures.…”
Section: Discussionsupporting
confidence: 92%
“…A mean MINORS criteria score of 9.8 [8–12] was reported. Six studies were classified as “excellent” ( 21 , 22 , 24 , 29 - 31 ), while the quality of the remaining studies was classified as “moderate” ( 17 - 20 , 23 , 25 - 27 , 31 - 34 ). No studies were classified as “very bad”.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 18 studies included, only 2 reported the preoperative HHS ( 18 , 19 ), while 12 mentioned only the postoperative HHS ( 20 - 22 , 25 - 27 , 29 , 30 , 31 - 34 ), and 4 did not report the HHS ( 23 , 24 , 28 , 31 ). The postoperative HHS had an average value of 78.1 [20–100].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations